Teachers’ Role in Preventing and Managing Bullying at SD Negeri 200117/26 Padangsidimpuan - Simangunsong, Nurzakiah; Sari, Novita; Ritonga, Hasna Dewi; Zona, Mara (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2023)
This is a qualitative study conducted at SD Negeri 200117/26 Padangsidimpuan. The subjects of this research are the school, class teachers, and students. Data collection techniques include observation, interviews, and documentation. Based on the research findings, the forms of student bullying behavior that occur include mocking peers. The role of teachers in addressing bullying in schools is as mediators and facilitators, where teachers bring together the parties involved in the conflict and call upon witnesses to explain the issues. Then, students involved in the problem are asked to apologize and reconcile. The role of teachers as guides is to provide guidance on bullying, and as advisors, teachers advise students who bully and advise bullying victims by providing motivation.